2010
DOI: 10.1111/j.1540-8183.2010.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Six‐ and Twelve‐Month Clinical Outcomes after Implantation of Prokinetic BMS in Patients with Acute Coronary Syndrome

Abstract: Clinical outcomes at 6 and 12 months after Prokinetic stent implantation are excellent and may be attributable to its unique combination of composition, design and coating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…In a recent randomized trial in ACS, a new generation coated BMS achieved a 12-month MACE rate which was non-inferior to an everolimus eluting stent, combined with a slightly higher TLR rate and lower definite stent thrombosis rate (9.6% vs. 9.0%, 6.5% vs. 4.9% and 0.7% vs. 2.2%) [36]. We observed similar results in our registry (8.4%, 5.0% and 0.7%), which are also in alignment with a single center study in ACS treated with a PRO-Kinetic stent (11.1%, 2.6% and 1.8%) [37]. The PROMETHEUS study assessed the safety and efficacy of the PROKinetic stent in patients with acute ST-elevation myocardial infarction (STEMI).…”
Section: Subgroup Analysissupporting
confidence: 93%
“…In a recent randomized trial in ACS, a new generation coated BMS achieved a 12-month MACE rate which was non-inferior to an everolimus eluting stent, combined with a slightly higher TLR rate and lower definite stent thrombosis rate (9.6% vs. 9.0%, 6.5% vs. 4.9% and 0.7% vs. 2.2%) [36]. We observed similar results in our registry (8.4%, 5.0% and 0.7%), which are also in alignment with a single center study in ACS treated with a PRO-Kinetic stent (11.1%, 2.6% and 1.8%) [37]. The PROMETHEUS study assessed the safety and efficacy of the PROKinetic stent in patients with acute ST-elevation myocardial infarction (STEMI).…”
Section: Subgroup Analysissupporting
confidence: 93%
“…76 A more recent study in patients with acute coronary syndrome (ACS) showed low rates for major events and re-interventions, despite the potentially higher risk of thrombosis in this group. 5 This Prokinetic stent (Biotronik) may also be benefiting from improved designs with thinner struts, compared to earlier coated devices. A drug-coated version is also available which elutes sirolimus from a biodegradable PLLA matrix.…”
Section: Non-pharmacological Stent Coatingsmentioning
confidence: 98%
“…As a reliable alternative, non-pharmacological solutions to address device restenosis; therefore, coating with silicon carbide, due to its semiconductor nature, demonstrates a reduction in inflammatory and thrombogenic responses [ 13 ]. The drug-coated version (sirolimus) of this technology is also available and shows significant clinical advantages [ 14 ]. The main target of this technology is the continuous protection of stents from restenosis after the drug elution and coating degradation are completed.…”
Section: Introductionmentioning
confidence: 99%